Low-temperature health hazards among workers of cold storage facilities in Lahore, Pakistan - Nadia Ghani; Foqia Tariq; Houda Javed; Numrah Nisar; Arifa Tahir (Nofer Institute of Occupational Medicine, 2020)
Background Cold storage facilities are the most common workplaces that produce artificially cold work environments and are associated with different adverse effects on human health, work productivity and the occurrence of accidents and injuries. The aim of this study was to measure the antagonistic health effects on workers, so that common factors causing abnormal symptoms could be determined, and to gather basic information to monitor the associated health risks from the exposure to cold work environments. Material and Methods A cross-sectional analytical study was conducted to investigate the occurrence of cold-related adverse health effects, musculoskeletal symptoms, skin problems, injuries, respiratory illnesses, general hygiene and occupational environment related to cold indoor workplaces, using the Standardized Nordic Questionnaire . A total of 200 subjects took part in this study, including 100 exposed and 100 unexposed to cold environments. A 1-way analysis of variance (ANOVA) and a t-test were applied to measure statistical differences and to differentiate the cases where variations occurred, using SPSS 16. Results The study revealed that a longer and constant exposure to extremely cold indoor work environments significantly increased (p < 0.001) the cold-related symptoms and musculoskeletal disorders which ultimately reduced (p < 0.01) the efficiency, effectiveness, performance and work ability of the exposed workers. Conclusions The study disclosed various adverse cold-related complaints of the studied subjects who were exposed to extreme cold conditions during a maximum number of working hours. The most consistent problems were related to musculoskeletal discomfort, skin problems and respiratory abnormalities. Med Pr. 2020;71(1):1-7